Corrosion mechanism of Al2O3–C stopper rod by calcium treated molten steel - Lidong Xing; Jingjing Liu; Yanping Bao; Min Wang (Journal of Materials Research and Technology)
The stopper rod plays a crucial role in continuous casting by controlling the flow of molten steel into the mold in the tundish, ensuring a stable molten steel level, and facilitating smooth operation. Despite its importance, limited research has been conducted on the corrosion mechanism of molten steel on stopper rods, particularly in the context of calcium treated molten steel. Herein, the difference of morphology, elemental composition, phase composition and distribution between the erosion layer and the substrate of stopper rod was studied by dissecting and characterizing the stopper rod. The microstructure of the erosion layer is more compact, while the microstructure of the substrate is relatively loose. Compared with the substrate, the erosion layer also contains Fe, (Ca, Al, Si) O and (Al, Mg) O phases. The specific phases in the erosion layer are MgAl2O4, Ca2(Al(AlSi)O7), and CaAl12O19. Laboratory simulation experiments show that stopper rod is very beneficial to the cleanliness of molten steel, but it will reduce the content of Ca, Mg, and Al elements in molten steel. As a result, the corrosion mechanism of calcium treated molten steel on Al2O3–C stopper rod was clarified.